Shaking table test and cumulative deformation evaluation analysis of a tunnel across the hauling sliding surface - Lifang Pai; Honggang Wu; Xu Wang (Deep Underground Science and Engineering, 2023)
Abstract To explore the cumulative deformation effect of the dynamic response of a tunnel crossing the hauling sliding surface under earthquakes, the shaking table test was conducted in this study. Combined with the numerical calculations, this study proposed magnification of the Arias intensity (MIa) to characterize the overall local deformation damage of the tunnel lining in terms of the deformation characteristics, frequency domain, and energy. Using the time‐domain analysis method, the plastic effect coefficient (PEC) was proposed to characterize the degree of plastic deformation, and the applicability of the seismic cumulative failure effect (SCFE) was discussed. The results show that the low‐frequency component (f1 and f2 ≤ 10 Hz) and the high‐frequency component (f3 and f4 > 10 Hz) acceleration mainly cause global and local deformation of the tunnel lining. The local deformation caused by the high‐frequency wave has an important effect on the seismic damage of the lining. The physical meaning of PEC is more clearly defined than that of the residual strain, and the SCFE of the tunnel lining can also be defined. The SCFE of the tunnel lining includes the elastic deformation effect stage (<0.15g), the elastic–plastic deformation effect stage (0.15g–0.30g), and the plastic deformation effect stage (0.30g–0.40g). This study can provide valuable theoretical and technical support for the construction of traffic tunnels in high‐intensity earthquake areas.